Manajemen Keuangan Publik Negara Indonesia dalam Perspektif Abu Yusuf - Mila Arlina, Agustin; Fageh, Achmad; Agus Hidayat, Ahmad (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
This study aims to to analyze the management of public financing by the Indonesian government, considering the principles of Maqashid Syariah and to explore Abu Yusuf's concepts and perspectives on taxation. The method used in this study was descriptive qualitative with a focus on library research. The findings of the study indicated that Abu Yusuf has three main sources of thoughts regarding public financing, specifically government income, including ghanima, shadaqah or zakat, and fay. In Indonesia, Abu Yusuf's ideas on public financing align with the inclusion of income tax revenue as part of the shadaqah criteria, land and building taxes categorized under Kharaj, and international trade taxes like import and export taxes classified as "Usyr".